(untitled) (Bangladesh Journal of Agricultural Research, 2016)
Combining ability and heterosis were studied in a 7×7 half diallel cross in maize for grain yield and yield contributing characters. Significant general and specific combining ability variances were observed for all the characters studied. The significant estimates of GCA and SCA variances suggested the importance of both additive and non-additive gene actions for the expression studied traits. In these studies, variances due to SCA were higher than GCA for all charactesr, which revealed the predominance of non additive gene action (dominance and epistasis) for controlling these traits. Parents P1 and P4 were excellent general combiner for days to tasseling and silking while P1 and P5 for early maturity. P4 for short height and, P4 and P7 for higher thousand kernel weight. The parents P4 and P6 having good combining abilities for yield. Heterosis estimation was carried out using two commercial varieties NK40 and 900MG. When standard commercial check NK40 was used, the percent heterosis for kernel yield varied from -51.39 to 12.53%. Among the 21 F1s, 3crosses exhibited significant positive heterosis for kernel yield. The highest heterosis was exhibited by the cross P4×P6 (12.43%), P6×P7 (10.89%) and P2×P3 (9.87%) respectively. Compared with 900MG as check, the percent heterosis for kernel yield varied from -53.73 to 7.01%. Among the 21 F1s, none of the crosses exhibited significant positive heterosis for kernel yield. The highest heterosis were exhibited by the crosses P4×P6 (7.01%), P6 x P7 (5.55%) and P2×P3 (4.57%). The crosses showed significant positive SCA values could be used for variety development after verifying them across the agro-ecological zones of Bangladesh. Bangladesh J. Agril. Res. 41(3): 565-577, September 2016